Iterative Decoding Algorithms for a Class of Non-Binary Two-Step Majority-Logic Decodable Cyclic Codes - Chang, Hsiu-Chi; Chang, Hsie-Chia (IEEE transactions on communications, 2014)
This paper presents two iterative decoding algorithms for a class of non-binary two-step majority-logic (NB-TS-MLG) decodable cyclic codes. A partial parallel decoding scheme is also introduced to provide a balanced trade-off between decoding speed and storage requirements. Unlike non-binary one-step MLG decodable cyclic codes, the Tanner graphs of which are 4-cycle-free, NB-TS-MLG decodable cyclic codes contain a large number of short cycles of length 4, which tend to degrade decoding performance. The proposed algorithms utilize the orthogonal structure of the parity-check matrices of the codes to resolve the degrading effects of the short cycles of length 4. Simulation results demonstrate that the NB-TS-MLG decodable cyclic codes decoded with the proposed algorithms offer coding gains as much as 2.5 dB over Reed-Solomon codes of the same lengths and rates decoded with either hard-decision or algebraic soft decision decoding.